2001
DOI: 10.1034/j.1399-6576.2001.045004421.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dopamine on porcine myocardial action potentials and contractions at 37 °C and 32 °C

Abstract: Cooling to 32 degrees C significantly prolongs the myocardial action potential and the contraction duration. Dopamine increases the contractile force and prolongs the action potential both at 37 degrees C and at 32 degrees C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Cooling of the myocardium also impacts both upon the contractility and the pacemaker function of the heart. In vitro cooling of porcine myocardium to 32°C causes a prolongation of contraction and an increase in contractile force by almost 40% 9. The hypertension of mild hypothermia is therefore a product of tachycardia, increased contractility and increased systemic vascular resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Cooling of the myocardium also impacts both upon the contractility and the pacemaker function of the heart. In vitro cooling of porcine myocardium to 32°C causes a prolongation of contraction and an increase in contractile force by almost 40% 9. The hypertension of mild hypothermia is therefore a product of tachycardia, increased contractility and increased systemic vascular resistance.…”
Section: Resultsmentioning
confidence: 99%
“…[21][22][23] In both animal experiments and human studies, these effects are dependent on the degree and duration of the hypothermia 22 23 ; all these findings are from anaesthetised or sedated subjects. During mild hypothermia, however, there is evidence of both increased 24 and reduced 25 contractility. We found that the stroke volume did not change with mild hypothermia, therefore changes in CO were fully explained by changes in HR.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the time elapsed for delivery of 3 pulses with 30 ms duration would be shorter that the reported action potential duration recorded in vitro in swine ventricle at physiological temperatures (> 100 ms; Roscher et al, 2001), it is possible that the in vivo conditions, such as transient myocardial ischemia and increased catecholamine release, resulting from the interruption of cardiac pumping during VF, may have resulted in action potential shortening (Christé et al, 2006;Hoeker et al, 2014). In this case, it is likely that defibrillatory pulses would reach some cells during the relative refractory period (vulnerable period), which would favor arrhythmia reinitiation (Corbisiero et al, 1999), thus masking or even reverting the beneficial effect of multidirectional defibrillation.…”
Section: Discussionmentioning
confidence: 99%
“…Pulse transformers (TP-1:1/4T, Thornton, Vinhedo, SP, Brazil) were used with chopped pulses to ensure that switching was triggered, and to isolate the high-voltage switching circuit from the low-voltage control circuit. The discharge switching circuit (one for each output, Figure 5a) was implemented by using bidirectional thyristors (triodes) for alternating current (TRIAC 226M, Power Innov., Inc., Lindon, UT, USA) sufficiently fast for delivery of up to 3 shocks within 60 ms (Figure 5b, c), i.e., in a shorter period than the duration of the absolute refractory period of action potential in the swine ventricle (Roscher et al, 2001). This ensures that a cardiac myocyte excited by one of the shocks will not be reexcited by the subsequent stimulus.…”
Section: The Multidirectional Defibrillatormentioning
confidence: 99%